Urban amusement parks of Midnapore (West Bengal, India): Utility, accessibility and structural diversity - Anirban Baitalik; Arnab Kumar Chakraborty; Tanmoyee Bhattacharjee (International Journal of Geoheritage and Parks)
Urban parks significantly enhance the urban residents' quality of life, offering spaces for recreation that positively impact physical and mental well-being. This comprehensive study, involving 400 diverse respondents, delves into urban park usage, visitor preferences, and attributes, shedding light on their crucial role in urban planning and community welfare. Demographic factors such as age, gender, religion, education, and health were analyzed, underscoring the importance of inclusive park design. Most participants frequented parks, favoring walking, biking, and motorbikes for transportation. While accessibility generally received positive feedback, some respondents faced challenges due to long travel times, hinting at potential distribution disparities. The study also explored willingness to pay for park access, revealing varying pricing opinions and aiding in sustainable park management decisions. Satisfaction levels varied across parks, with higher scores associated with diverse green spaces, well-maintained facilities, and safety measures. Preferences were influenced by factors like distance and cost. Structural diversity analysis highlighted varying degrees of diversity among parks, emphasizing the importance of diverse amenities, accessible design, and sustainable management practices. These insights offer valuable guidance for urban planners and park authorities to address community needs and foster well-being and community connection in urban spaces.